Time Series Forecasting by Using Box-Jenkins Models - Gorgess, Hazim M.; brahim, Raghad I (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we introduce a brief review about Box-Jenkins models. The acronym ARIMA stands for â€œautoregressive integrated moving averageâ€. It is a good method to forecast for stationary and non stationary time series. According to the data which obtained from Baghdad Water Authority, we are modelling two series, the first one about pure water consumption and the second about the number of participants. Then we determine an optimal model by depending on choosing minimum MSE as criterion.